Impact of urban-rural integration on resource misallocation in old industrial cities and its mechanisms - ZHU Gaoli, SHENG Li (Ziyuan Kexue)
[Objective] This study examined the issue of resource misallocation in old industrial cities from the perspective of urban-rural integration. It aimed to provide new strategies for optimizing resource allocation and promoting balanced economic development, contributing to the economic transformation of old industrial cities. [Methods] Based on the panel data from 95 old industrial cities in China (2008-2020), the study empirically tested the overall and heterogeneous effects of urban-rural integration on resource misallocation. It explored the mediating role of industrial structure transformation and upgrading and used a threshold effect model to analyze the dynamic impacts of urban-rural integration on resource misallocation. [Results] (1) Urban-rural integration helped to improve resource misallocation. Heterogeneity tests revealed that urban-rural integration improved resource misallocation across cities in different regions and of different development levels, but the degree of improvement varied. Specifically, the improvement was strongest in eastern regions, followed by central regions, and was weakest in western and northeastern regions. Similarly, second- and third-tier cities experienced greater improvements than fourth- and fifth-tier cities. (2) Mechanism analysis showed that industrial structure upgrading and industrial structure optimization partially mediated the relationship between urban-rural integration and resource misallocation. When the levels of industrial structure upgrading and optimization were below the second threshold value, urban-rural integration hindered the improvement of resource misallocation. However, once these levels exceeded the second threshold value, the impact of urban-rural integration on resource misallocation shifted from hindrance to improvement. (3) Further analysis indicated that the intensity of urban-rural integration policy implementation played a positive moderating role in the relationship between urban-rural integration development and resource misallocation. [Conclusion] Urban-rural integration significantly improved resource misallocation in old industrial cities by promoting industrial structure transformation and upgrading. Its effects were influenced by regional differences, city tiers, and the threshold effects of industrial structure transformation. The intensity of policy implementation further strengthened the improvement effect. To fully address resource misallocation in old industrial cities, differentiated urban-rural integration policies should be developed based on regional characteristics and city tiers, promoting industrial structure optimization and precise policy implementation.